2019
DOI: 10.1111/imb.12556
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase 2 is a functional receptor of Cry1Ac but not Cry2Ab in Helicoverpa zea

Abstract: Although membrane‐bound alkaline phosphatases (ALPs) have been proposed as a receptor for Cry1Ac in a few lepidopteran species, their potential functions as a Cry2Ab receptor are yet to be verified. To determine if ALP2 also serves as a receptor for Cry1Ac and even for Cry2Ab in Helicoverpa zea, we measured the potency of activated Cry1Ac and Cry2Ab against midgut and fat body cell lines of H. zea and the ovarian cell line of Spodoptera frugiperda (Sf9) expressing H. zea ALP2 (HzALP2) or transfected with HzALP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
(75 reference statements)
0
22
0
Order By: Relevance
“…Meanwhile, the up-or downregulation of these receptors have been reported to be involved in the insect resistance to Cry toxins (Atsumi et al, 2012;Baxter et al, 2011;Chen et al, 2015;Gahan, Pauchet, Vogel, & Heckel, 2010;Jurat-Fuentes et al, 2011;Tiewsiri & Wang, 2011;Xiao et al, 2014;Xu, Yu, & Wu, 2005;Zhang et al, 2009). Along with the further research, more new receptor proteins, new genes, and resistance pathways are being reported to be involved in the toxicity of Bt and the resistance mechanisms of insects (Heckel, 2012;Wei, Zhang, Liang, & Li, 2018).…”
mentioning
confidence: 99%
“…Meanwhile, the up-or downregulation of these receptors have been reported to be involved in the insect resistance to Cry toxins (Atsumi et al, 2012;Baxter et al, 2011;Chen et al, 2015;Gahan, Pauchet, Vogel, & Heckel, 2010;Jurat-Fuentes et al, 2011;Tiewsiri & Wang, 2011;Xiao et al, 2014;Xu, Yu, & Wu, 2005;Zhang et al, 2009). Along with the further research, more new receptor proteins, new genes, and resistance pathways are being reported to be involved in the toxicity of Bt and the resistance mechanisms of insects (Heckel, 2012;Wei, Zhang, Liang, & Li, 2018).…”
mentioning
confidence: 99%
“…Cell mortality was calculated with the Abbott formula (Abbott, 1925) as the description in Wei et al (2016Wei et al ( , 2019b). Significant differences in cell mortalities, relative expression level, and enzyme activities of HaCAN between CAN-GFP-pIEx (dsCAN) and GFP-pIEx (dsEGFP) were compared using Student's t-test (DPSSOFT: DPS7.05).…”
Section: Discussionmentioning
confidence: 99%
“…Helicoverpa zea midgut cell line RP-HzGUT-AW1 (MG) was generously provided by Dr. Xianchun Li (University of Arizona, Tucson, AZ, United States) (Goodman et al, 2004). Spodoptera frugiperda cell line (Sf9) and MG cell line were routinely maintained at a constant temperature incubator, and the culture mediums were prepared as the description in Wei et al (2016Wei et al ( , 2018aWei et al ( , 2019b.…”
Section: Insects and Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations